1995
DOI: 10.1038/bjc.1995.100
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin sensitivity and thermochemosensitisation in thermotolerant cDDP-sensitive and -resistant cell lines

Abstract: Summary Development of thermotolerance is an important phenomenon that must be considered when thermochemotherapy with multiple heat treatments is used clinically. To study the effect of thermotolerance on cellular cisplatin (cDDP) sensitivity at 3rC and 43-C in cell lines with different cDDP sensitivities, two Ehrlich ascites tumour cell lines (one with high cDDP sensitivity and one with in vitro acquired cDDP resistance) were used. The results indicate that in both cell lines the state of thermotolerance per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Based on the data given in Figure 2, the thermal enhancement ratios (TERs) at 90% survival, corrected for hyperthermic killing alone, were calculated. For cisplatin (TER 3.5), similar numbers indicating a marked sensitization were also reported by Hettinga et al [25], using Ehrlich ascites tumor cells. For antimetabolites such as 5-fluorouracil, a limited increase of cytotoxicity at hyperthermic temperatures has been suggested, based on the fact that these drugs require an intact cellular metabolism which is known to be reduced during hyperthermia [26].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Based on the data given in Figure 2, the thermal enhancement ratios (TERs) at 90% survival, corrected for hyperthermic killing alone, were calculated. For cisplatin (TER 3.5), similar numbers indicating a marked sensitization were also reported by Hettinga et al [25], using Ehrlich ascites tumor cells. For antimetabolites such as 5-fluorouracil, a limited increase of cytotoxicity at hyperthermic temperatures has been suggested, based on the fact that these drugs require an intact cellular metabolism which is known to be reduced during hyperthermia [26].…”
Section: Discussionsupporting
confidence: 78%
“…These results suggest an attenuated thermal sensitization for all of the chemotherapeutics tested during the status of thermotolerance. In this regard, Hettinga et al [25] reported similar findings in cisplatin-resistant and -sensitive cells.…”
Section: Discussionsupporting
confidence: 59%
“…Under several conditions, including thermo tolerance, a good correlation has been found between the extent and duration of this ``nuclear protein aggregation`` and thermal cell rilling (Hettinga et al, 1995). This nuclear protein aggregation may also be one of the major mechanisms responsible for thermal potentiation of killing by a number of drugs, which is by hampering repair of drug-induced DNA damage (Hettinga et al 1995). Timing of chemotherapy, with respect to potentiation by heat, and of two drugs relative to each other, is critical in determining antitumor efficacy, toxicity, and survival (Bull et al, 2008b;Teischer and Herman, 1992).…”
Section: The Rationale For Cisplatin and Laser Thermal-therapy For Camentioning
confidence: 99%
“…This leads to an increase in protein mass of nuclei isolated from heated cells. Under several conditions, including thermo tolerance, a good correlation has been found between the extent and duration of this ``nuclear protein aggregation`` and thermal cell rilling (Hettinga et al, 1995). This nuclear protein aggregation may also be one of the major mechanisms responsible for thermal potentiation of killing by a number of drugs, which is by hampering repair of drug-induced DNA damage (Hettinga et al 1995).…”
Section: The Rationale For Cisplatin and Laser Thermal-therapy For Camentioning
confidence: 99%
See 1 more Smart Citation